2016
DOI: 10.3389/fbioe.2016.00084
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Cochlear Implant Patient-Specific Model of the Voltage Distribution in a Clinical Setting

Abstract: Cochlear Implants (CIs) are medical implantable devices that can restore the sense of hearing in people with profound hearing loss. Clinical trials assessing speech intelligibility in CI users have found large intersubject variability. One possibility to explain the variability is the individual differences in the interface created between electrodes of the CI and the auditory nerve. In order to understand the variability, models of the voltage distribution of the electrically stimulated cochlea may be useful.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 37 publications
(79 reference statements)
0
45
0
1
Order By: Relevance
“…For each nerve fiber, the activation function in the most peripheral nerve was computed as in Eq. 4 from Nogueira et al (2016). The currents delivered to each electrode across time, also known as electrodograms, for…”
Section: Excitation Patterns Using Sequential Paired and Triplet Stimentioning
confidence: 99%
See 1 more Smart Citation
“…For each nerve fiber, the activation function in the most peripheral nerve was computed as in Eq. 4 from Nogueira et al (2016). The currents delivered to each electrode across time, also known as electrodograms, for…”
Section: Excitation Patterns Using Sequential Paired and Triplet Stimentioning
confidence: 99%
“…Finally, the neural excitation patterns, i.e. the neural activity across time, were computed using the nerve fiber model described in Nogueira et al (2016) which is very similar to the one presented by Litvak et al (2007). German tokens were processed with the Sequential, Paired and Triplet sound coding strategies using the same levels of stimulation (threshold and most comfortable levels).…”
Section: Excitation Patterns Using Sequential Paired and Triplet Stimentioning
confidence: 99%
“…Although in-silico studies have not been commonly applied into the clinical practice of CI, they have shown their potential to become valuable tools to compute predictive performance of the implantable device [6][7][8][9]. In the past, some authors assessed the resulting electric field accounting for different cochlear implant set-ups, such as stimulation protocols [10][11][12], or neural fiber conditions, contrasting both intact and degenerated fibers [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not lead to a complete and automatic computational approach encompassing all stages, from the generation of a highly detailed patient-specific model of the cochlear anatomy to the neural response evaluation. Some previous studies considered volume conduction models from simplified [7,16] and parametric [9] representations of the cochlear anatomy, built from guinea pig cochleae [19], or considered a more detailed geometrical model [20]. However, simplified or generic models limit the insight on CI performance, due to their high dependence on patient-specific factors, pointing out to the need for personalized detailed models [20].…”
Section: Introductionmentioning
confidence: 99%
“…A computational model has been designed to make quantitative predictions of loudness and pitch perception using the DC-VC mode (Nogueira et al, 2016). Computational models have been successfully used to investigate multipolar stimulation in the implanted cochlea (e.g.…”
Section: Introductionmentioning
confidence: 99%